Pendidikan Kesehatan sebagai Upaya dalam Pengendalian Hipertensi Guna Meningkatkan Kemandirian pada Lansia - Putra, I Gede Yudiana; Muryani, Ni Made Sri; Ni Putu Eka Febianingsih (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Background: Elderly individuals with uncontrolled high blood pressure are at high risk for developing complications. One of the prevention efforts for hypertension complications is regular blood pressure monitoring. Blood pressure control and prevention of hypertension complications are influenced by several factors, including the patient's knowledge of hypertension and dietary patterns. Through understanding, early detection, and appropriate treatment, elderly individuals can manage and prevent serious complications that may arise. Methods: The activity implementation stage includes preparation of facilities and equipment, followed by health education using educational video media and leaflets. The activity was held in one session. The target audience for this activity was elderly individuals, both independent and assisted, aged 45 years and older. Evaluation was conducted using pre- and post-tests. Results: The activity was carried out at Wantilan, Desa Guwang, with the attendance of 30 elderly individuals from the local elderly group in the village. The activity began with elderly exercise, followed by health education through an educational video and leaflet distribution. The pre-test and post-test results showed a significant improvement in the elderly's knowledge about hypertension. The elderly demonstrated a better understanding of hypertension, including the definition of normal blood pressure, how to measure blood pressure, and the importance of a healthy lifestyle to control hypertension. Conclusion: Health education is crucial in controlling hypertension in the elderly. With accurate knowledge about hypertension, the elderly become more confident in taking preventive actions. Increased independence has a positive impact on physical, mental, and emotional aspects, which helps the elderly feel more optimistic and have a better quality of life.